2018
DOI: 10.1177/0003489418789178
|View full text |Cite
|
Sign up to set email alerts
|

Grill-Cleaning Wire Brush Bristle Ingestion: Case Series and Review of the Literature

Abstract: Case Series, IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 10 publications
0
29
0
Order By: Relevance
“…3 Subsequent cases have included pediatric and adult patients and noted that ingested bristles were commonly located in the base of the tongue, esophagus, palatine tonsils, parapharyngeal space, vallecula, and in the gastrointestinal tract. 1,4–13…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…3 Subsequent cases have included pediatric and adult patients and noted that ingested bristles were commonly located in the base of the tongue, esophagus, palatine tonsils, parapharyngeal space, vallecula, and in the gastrointestinal tract. 1,4–13…”
Section: Discussionmentioning
confidence: 99%
“…7 Regardless of the retrieval modality, close to 40% of first attempts at removing the bristle have been unsuccessful and close to 22% have required open neck exploration to remove the foreign bodies. 1 Harlor et al 10 and Mortensen et al 1 have suggested the use of contrasted imaging to localize bristles that have migrated, especially those close to vascular structures in the head and neck. We also believe that a contrasted CT with 1–2 mm cuts better highlights anatomy and is more suited for operative planning.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations